Challenging school libraries in Portugal: compromise, consideration, communication and collaboration - Bastos, Glória (2011)
School libraries in Portugal are facing several problems concerning their integration in school’s culture. This situation is due to different factors, which I intend to analyse in this paper. The first one comes from central administration and the institutionalization of the role of teacher librarian. At the school level, the commitment of school administrators and the collaboration with classroom teachers also need special attention.